Roseomonas ponticola sp. nov., a novel bacterium isolated from Pearl River estuary. Issue 10 (8th October 2021) - Yin, Ling-Zi; Li, Jia-Ling; Fang, Bao-Zhu; Liu, Ze-Tao; Wang, Pandeng; Dong, Lei; Duan, Li; Luo, Xiao-Qing; Li, Shan-Hui; Li, Wen-Jun
Abstract : A novel species of the genus Roseomonas, designated SYSU M41301 T, was isolated from water sample of the Pearl River estuary in Guangdong, China. Polyphasic, taxonomic and phylogenomic analyses were used to determine the taxonomy position of the strain. Phylogenetic analysis using 16S rRNA gene sequence indicated that strain SYSU M41301 T showed the highest sequence similarity to Roseomonas stagni KCTC 22213 T (97.9 %) and Roseomonas riguiloci KCTC 23339 T (96.4 %). The novel species could be differentiated from other species of the genus Roseomonas by its distinct phenotypic and genotypic characteristics. The isolate was Gram-staining-negative, aerobic, short rod-shape, oxidase-positive and non-motile. The predominant respiratory quinone was ubiquinone 8 (Q-8). The major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylcholine, and one unidentified polar lipid. The major fatty acids (>10 % of total) were 11-methyl C18 : 1  ω 7 c, summed feature 3 (C16 : 1  ω7 c and / or C16 : 1  ω6 c) and summed feature 8 (C18:  :1  ω 7 c and/or C18 : 1  ω 6 c ). The G+C content of the novel isolate based on genomic DNA was 72.0 mol%. On the basis of phenotypic, genotypic and phylogenetic data, strain SYSU M41301 T should be considered to represent a novel species in the genus Roseomonas, for which the name Roseomonas ponticola sp. nov. is proposed with the type strain SYSU M41301 T (=KCTC 72726 T =CGMCC 1.18613 T ).